The Role of Human Resource Management in Implementing a Recruitment and Selection System for Competitive Advantage - Nuryani, Yusrianingsih; Zayroni, Ahmad; Santoso, Ayyub; Anshori, Mochammad (Economic and Business Horizon, 2023)
Butterfly pea flower has properties as an antioxidant, antidiabetic, hepatoprotective, anti-obesity, anti-inflammatory, and anticancer. To ensure the safety of the medication, toxicity testing is required. Acute toxicity testing can be used to assess the effects caused by toxicity on target organs, with the frequently observed target organ being the liver. Acute liver toxicity parameters can be observed by measuring the levels of bilirubin, SGOT, and SGPT. The purpose of this research is to look for signs of acute toxicity after the administration of ethanol extract of butterfly pea flower in test animals, determine the LD50 of the ethanol extract of butterfly pea flower in acute toxicity testing, and assess the impact of the ethanol extract of butterfly pea flower on test animals regarding bilirubin levels. The re-maceration method was used to create the ethanol extract from butterfly pea flowers, and a fixed-dose method was used for the acute toxicity testing. The research results showed that the butterfly pea flower extract with a dose of 2000mg/kgBW did not exhibit any symptoms of acute toxicity. The LD50 value for a dose of 2000mg/kgBW was classified as moderately toxic, and there was a significant impact on bilirubin levels with a significance value (2-tailed) of <0.05, which is 0.003, whereas SGOT and SGPT levels did not show a significant impact with values >0.05, which are 0.759 for SGOT and 0.324 for SGPT.